Implementasi Kurikulum 2013 Revisi Dalam Mengembangkan Kualitas Pembelajaran Pada Mata Pelajaran Al-Qu’ran Hadits Kelas VIII Di MTs Swasta Al-Washliyah Pangkalan Brandan - Devi Indah Sari Chaniago, Muhammad Saleh, Zaifatur Ridha (ALACRITY : Journal of Education, 2023)
The problem that was found when the researcher made observations was the teacher's lack of understanding about the application of the Revised 2013 curriculum to the Al-Qur'an Hadith subject in an early learning theme because the Revised 2013 curriculum had not been socialized optimally. Limited learning facilities and infrastructure such as the unavailability of language and computer laboratories that can be used as creative and innovative learning spaces in learning by implementing the Revised 2013 curriculum. The difficulty of teachers in the field of Al-Qur'an Hadith studies in combining learning quality improvements in the form of increasing students' intellectual, spiritual and emotional competencies. Based on the background of the problem, the researcher uses qualitative research methods to facilitate researchers in describing the results of research conducted using data collection techniques in the form of interviews, observation and documentation. The results of the conclusions from this study are: That the implementation of the 2013 curriculum revision in learning Al-Qur'an Hadith in class VIII MTs Al-Washliyah has been going well through the stages in implementing the 2013 curriculum. The revision is carried out through a process of planning, action, evaluation . One of the leading programs in implementing the Revised 2013 curriculum in Al-Qur'an Hadith learning is by holding the following programs: Holy Qur'an, namely learning to read the Al-Qur'an specifically for students who are not yet able to read the Al-Qur'an in accordance with the tajwid and makhraj hurf in accordance with the rules of reading the Qur'an. Tahfiz Qur'an, namely Al-Qur'an Hadith learning with the target of training students' ability to memorize verses of the Al-Qur'an. Tahfiz Qur'an Express, namely implementing Al-Qur'an memorization learning in the Al-Qur'an Hadith study field in accordance with the technical instructions for learning and adjusting to the Learning Implementation Plan (RPP) in the Al-Qur'an Hadith study field.